Pengaruh perbedaan kadar larutan klorheksidin 0,1% dan 0,2% terhadap warna mahkota tiruan sementara berbahan bis-acryl composite - Rizky Lesmana, Muhamad; Elias, Suzan; Sarwono, Aditya (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Background: Chlorhexidine mouthwash is widely used by some Indonesians as a gargling solution to maintain healthy teeth and oral cavity. The use of provisoris is one of the important stages in the making of artificial crowns. One of the commonly used materials is bis-acryl composite because the manufacturing process is easier and has good aesthetics. However, this material also has disadvantages, such the high price and high water absorption rate. This can affect the discoloration of the surface of the bis-acryl composite. Aim: To determinate effect of differences of 0,1% and 0,2 % chlorhexidine solution levels on the color of temporary crown material bis-acryl composite. Methods: This study used a laboratory experimental method with pretest-posttest designs. The samples used were 30 samples with a diameter of 10 mm and a height of 2 mm which were divided into 3 large groups. 10 samples each for immersion in artificial saliva, 10 samples for immersion in artificial saliva and 0.1% chlorhexidine, and 10 samples for immersion in artificial saliva and 0.2% chlorhexidine for 10 days and stirred for 2 minutes. After immersion, the sample was tested for color changes using a spectrophotometer VITA Easyshade Advance 4.0. Data were analyzed by paired t test and Wilcoxon test. Result: The results of paired t test and Wilcoxon test showed that there was a significant color change (p < 0.05) only in the C value of the artificial saliva and 0.2% chlorhexidine before and after treatment. Conclusion: 0.2% chlorhexidine gave a temporary artificial crown chroma discoloration made from bis-acryl composite.